The intersection of Islamic microfinance and women's empowerment: A case study of Baitul Maal Wat Tamwil in Indonesia - Ninik Sri Rahayu (International Journal of Financial Studies, 2020)
It is largely assumed that Islamic microfinance institutions (IMFIs) deal with family empowerment instead of women's empowerment. However, women are the main beneficiaries of Baitul Maal Wat Tamwil (BMT), Indonesia's first IMFIs. This paper aims to explore the origins, the initiators, and the visions of BMTs and the extent to which they intersect with women's empowerment. Employing a qualitative approach, this study selected four BMTs in Yogyakarta as a case study. It found that four critical groups that have a significant role in the development of Indonesian BMTs: ICMI (Association of Indonesian Muslim Intellectual), Islamic mass organizations, NGOs, and local governments. The issues of loan sharks and poverty alleviation were the primary factors driving the inception of BMTs. Despite women being crucial clients, none of the studied BMTs explicitly invoked women's empowerment in their organizational vision. To conclude, the BMTs' preference for women is not based on an understanding of gender inequality, but rather motivated by pragmatic business considerations, particularly the self-sustainability paradigm that underpins their practices.
Keywords: G21; G23; G29; 330; women's empowerment; Baitul Maal Wat Tamwil; Islamic microfinance